An evaluation of the microbiological cleanliness of the herbal blood purifier compositions sold in India by Ayurvedic Physicians. - Kazi, Sarfaraz; Pore, Amol; Raut, Yogesh; Dongare, Gopika; Jadhao, Kailas; Bais, Sanjay (Journal of Neonatal Surgery, 2025)
Background: Herbal blood purifier requires for the purification of blood which is sold by Ayurvedic Physicians. Objective: Consumers are using unregistered herbal goods through Ayurvedic Physicians in order to alert them to the possibility of contamination of herbal products. Method: The pour plate method was the one used in this investigation. At 37°C, the particular medium dishes were left to incubate for 24 hours. The plate of culture was placed on a colony counter and checked for microorganisms there. Result: While formulae with the code numbers BP3,BP5, BP6,BP10had excessive levels of Staphylococcus aureus contamination, ingredients with the code numbers BP1,BP2 and BP8, BP9 were found to have excessive amounts of Pseudomonas aeruginosa and Escherichia coli contamination. Conclusion: When dealing with therapeutic herbs for human consumption, the suggestions of the current research should be considered. The findings recommended that regular and systematic qualitative evaluation of extracted herbal materials is required to find out the over limits of heavy metal contaminants and microbial contamination before using them for human use or the processing for finished products of herbal drug dosages, so that possible heavy metal impurities does not reach to the herbal products..